The political economy of Zambia’s recovery: Structural change without transformation? - Resnick, Danielle; Thurlow, James (International Food Policy Research Institute, 2014)
Using the case of Zambia, this paper examines whether structural change translates into reduced poverty and improved social welfare through an empirical and systematic analysis of the country’s growth trajectory during 1991–2010. We find that growth after 2002 was accompanied by positive structural change, but most new jobs were in the low-wage, insecure informal sector in urban areas. Due to the demands of an expanding middle class, construction and high-value services also generated additional jobs, but the share of employment growth from these sectors was small and skewed more toward higher-skilled Zambians. Consequently, for a majority of the population, large-scale social transformation did not follow from structural change.